Supported structure-controlled graphitic carbon nitride catalyst for dehydrochlorination of 1, 2-dichloroethane. Issue 20 (25th September 2018) - Sun, Xi; Qin, Yucai; Li, Qiang; Liu, Xi; Liu, Zheng; Song, Lijuan; Sun, Zhaolin
Abstract : The activated carbon supported carbon nitride with more 'defects' shows higher catalytic activity for dehydrochlorination of 1, 2-DCE than the one with a high degree of polymerization. Abstract : Pyrolysis of dichloroethane is an important reaction for the production of vinyl chloride monomer. The high operating temperature and low efficiency are, however, nuisances for this process. In this manuscript, a supported structure-controlled graphitic carbon nitride is reported as a highly efficient catalyst for dehydrochlorination of 1, 2-dichloroethane (1, 2-DCE). The results indicate that the "defects" of the active component, i.e., the chain terminations of the carbon nitride, which tend to form at low synthesis temperature of the catalyst, show high catalytic activities for the dehydrochlorination of 1, 2-dichloroethane, while for the high degree of polymerization of carbon nitride, which tends to increase at high synthesis temperature, relatively low activities for the reaction can be found. These findings highlight the role of the "defects", i.e., chain terminations, of the material in the reaction and also provide a strategy for the selective synthesis of highly active N-doped carbon catalysts for this reaction.